New Generation User Interface based on Hand Tracking in 3D Space - Serafinavičius, P.; Sajauskas, S. (Elektronika ir Elektrotechnika, 2010)
The hand tracking system in 3D space dedicated for design of new generation user interface is presented. The system is based on 3D computer vision and implemented using open source computer vision library (OpenCV). The further experimental evaluation of the system was performed closer as possible to meet the real environment conditions. The system is able to detect and track user’s head and hand and return 3D coordinates in real time. The detection of head and hand is based on adapted Viola-Jones detector. The detection rate is equal to (91 ± 2)%. The tracking is based on Lucas-Kanade optical flow calculation technique which was customized and improved for hand tracking. High tracking robustness ((93 ± 2)%) was achieved. Small variations of the robustness rate, while changing ambient lighting type, intensity and background conditions, are acceptable for alternative computer vision-based user interface. Ill. 8, bibl. 5 (in English; abstracts in English, Russian and Lithuanian).